2022
DOI: 10.1094/pdis-10-21-2158-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Leaf Spot Disease of Tobacco Caused by Pseudomonas cichorii in China

Abstract: Tobacco (Nicotiana tabacum L.), one of the chief commercial crops, is wildly cultivated worldwide. In June 2020 and 2021, an unknown bacterial leaf spot on tobacco was found in Hezhou and Hechi City, Guangxi, China. 30% of the tobacco were affected and the rate of diseased leaves reached about 10% in the field under high temperature and rainstorm. The disease mainly damaged the middle and top leaves of tobacco plants at vigorous growing stage. The initial symptoms were water-soaked spots on the frontal half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…These results provide insights for exploring the causes of P. tunicoides disease. Interestingly, Chernin et al found that Enterobacter suppresses the growth of different pathogenic fungi [ 36 ], while Pseudomonas is involved in bacteriostasis of root rot, has plant colonization characteristics, and exhibits antagonistic properties against soil-borne plant pathogenic fungi [ 37 ]. The most abundant healthy plant bacterial genera in P. tunicoides was Bradyrhizobium (12.95%).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide insights for exploring the causes of P. tunicoides disease. Interestingly, Chernin et al found that Enterobacter suppresses the growth of different pathogenic fungi [ 36 ], while Pseudomonas is involved in bacteriostasis of root rot, has plant colonization characteristics, and exhibits antagonistic properties against soil-borne plant pathogenic fungi [ 37 ]. The most abundant healthy plant bacterial genera in P. tunicoides was Bradyrhizobium (12.95%).…”
Section: Discussionmentioning
confidence: 99%